Short implants with single-unit restorations in posterior regions with reduced height - a retrospective study - Jamal Hassan Assaf; Agenor Montebello Filho; Fabricio Batistin Zanatta (Universidade Estadual de Campinas, 2015)
Aim: Previous studies have shown excellent prognosis with short implants. However, evidence of short implants rehabilitated with single-unit restorations is scarce. The purpose of this study was to evaluate the percentage of success of short implants in posterior maxillary and mandibular regions with single-unit restorations. Methods: This study comprised a retrospective analysis of data of 41 patients that received 54 short implants between 2004 and 2009. All implants were placed by the same surgeon and all restorations were performed by experienced professionals. All implants were placed in sites with reduced bone volume; 48 implants were evaluated by computed tomography and 6 implants by radiography. Failures and biological complications were analyzed. Results: It was observed a success rate of 96.3% in the osseointegration period and 100% in the load period that ranging from 7 to 38 months. Two complications were observed, which were successfully treated without risk of implant loss. Conclusions: Short implants in posterior regions rehabilitated with single-unit restorations are a treatment option with high success rate and thus may be indicated in posterior regions with reduced bone height.